Custos e benefícios para uma empresa de distribuição de energia elétrica decorrentes da inserção de geração distribuída - Fiuza, Evandro Lucio (2022)
Due to greater penetration of distributed generation (DG) and the recent regulatory transition, electricity distribution companies (DISCO) in Brazil have been looking for new forms of their new business, aiming to reduce the financial risk arising from the business of increasing complexity and, consequently, of costs. However, for the DISCO there are not many available tools to do a test ex-ante of the business model, it is a barrier to identify in a systematic way the cost and benefits of DG on the distribution system. In this way, the present work of planning three taxonomies to assist the distributor in this process. For this reason, a qualitative survey with carried out through the software Atlas.TI, in an exhaustive, looking for secondary data related to costs and benefits of DG for distributors. The factors were typified and classified using three proposals of taxonomies and considering different regulatory environments. The results show what are the factors of difficulty that DG imposes on the distribution system, which also determine the cost and/or income to the DISCO, and the conditions for this happened. The quantification of these costs and revenues will allow the distributor to run out baseline tests of business model helping in the incorporation of DG.